1982
DOI: 10.1897/1552-8618(1982)1[347:poctfa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Chronic Toxicity From Acute Toxicity of Chemicals in Fish and Aquatic Invertebrates

Abstract: The relationship of the acute LC,, of chemicals to their chronic toxicity for aquatic animals can be expressed as the acute chronic ratio (ACR). Based on ACR data accumulated from the literature, the size ranges of ACRs for various chemicals were determined for different species. The relationship and significance of the size of the ACR for various species, LC,, values, bioconcentration factors, classes of chemicals and their uses and mode of toxic action are given. Eighty-six percent of the LC,, acute toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 4 publications
6
58
2
Order By: Relevance
“…For both Zn and Pb, the effects increased by a factor 4 when the exposure period was increased from 48 h to 10 weeks. Kenaga (1982) calculated acute-to-chronic ratio's (ACR) based on LCs0's for several toxicants. The few data available for invertebrates, mainly Daphnia, suggest that these ACR's are much higher for non-essential metals than for essential metals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both Zn and Pb, the effects increased by a factor 4 when the exposure period was increased from 48 h to 10 weeks. Kenaga (1982) calculated acute-to-chronic ratio's (ACR) based on LCs0's for several toxicants. The few data available for invertebrates, mainly Daphnia, suggest that these ACR's are much higher for non-essential metals than for essential metals.…”
Section: Discussionmentioning
confidence: 99%
“…for the freshwater mussel Corbicula manilensis the LCs0 for Cu decreased with increasing exposure time (Harrison et al, 1984). Kenaga (1982) calculated acute-chronic ratios (ACR; the acute ECs0 divided by the chronic ECs0) for a number of substances and organisms and demonstrated that for Daphnia magna the ACRs for Pb and Cd were much higher than for Zn and Cu, possibly because Cu and Zn are essential metals, whereas Pb and Cd are not known to have any biological function. Kraak et al (1992) observed that the ECs0 for Cd for filtration rate of the zebra mussel Dreissena polymorpha decreased when exposure time was increased from 48 h to 10 weeks, whereas the effects of Cu did not increase during prolonged exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The SSDs for cadmium in soil, river water, river sediment, coastal water, and coastal sediment (Fig. 4) were constructed with EC 50 /LC 50 / IC 50 values which were divided by a safety assessing factor (the factor is equal to 5 in this case (Kenaga, 1982;Maltby et al, 2005) to determine the sensitivity of terrestrial, river aquatic and benthic, coastal aquatic and benthic organisms.…”
Section: Effects Assessmentmentioning
confidence: 99%
“…This does not appear to be a serious concern because acute responses have been shown to be effective predictors of chronic effects of both a carcinogenic (5) and noncarcinogenic nature (3,4,6,7). In fact, the chronic no-observed adverse effect level in mammalian models and the chronic maximum acceptable toxicant concentration in fish have been similarly estimated by dividing the acutely lethal dose (LD50/LC50) by approximately 50-75 (4,6,7,8). These data show a high degree of fundamental concordance between fish and mammalian responses with respect to the capacity of acute doses to estimate chronic responses.…”
Section: Tainty-------------------------mentioning
confidence: 99%